Fair. - Barrett, Claire; Comer, Stuart; Cummings, Neil; Farquharson, Alex; Gleadowe, Teresa; Gortzak, Roos; Goux, Jean-Joseph; Graw, Isabelle; Hickey, Dave; Higgs, Matthew; Hunt, Andrew; Hutchison, Daisy; et al. (London : Royal College of Art, 2002)
Bell, Dirk ; Braun, Matti ; Kunath, Friedrich E. ; Dahn, Walther ; Pocock, Philip ; Roehr, Peter ; Alexander, Andy ; Cooley, Mason ; Fisher, Kim ; Munro, JP ; Taylor, Stephanie ; Ayzenberg, Valeriy ; Litvin, Anton ; Mamonov, Bogdan ; Morozova, Lisa ; Alom, Juan Carlos ; Aparicio, Eduardo ; Armada, Santiago ; Bruguera, Tania ; Ceballos, Sandra ; Fernández, Alfredo Ramos ; Garaicoa, Carlos ; Marrero, Jorge Luis ; Padura, Maria Cristina ; Quintana Bravo, René ; Ramos, Sandra ; Rives Ruiz, Michelle ; Althamer, Pawel ; Krasinski, Edward ; Sasnal, Wilhelm ; Sosnowska, Monica ; Uklanski, Piotr ; Akakce, Haluk ; Ataman, Kutlug ; Cavusoglu, Ergin ; Erkmen, Ayse ; Abaroa, Eduardo ; Cruzvillegas, Abraham ; Cuevas, Minerva ; Guzman, Daniel ; Hernandez, Jonathan ; Hernandez, Philippe ; Kuri, Gabriel ; Lopez Ramirez, Jeronimo ; Orozco, Gabriel ; Ortega, Damián ; Ortega, Fernando ; Ortega, Luis Felipe ; Táboas, Sofia ; Geschwind, Peter ; Grantsaan, Gillion ; Ketara, Tiina ; Schulenburg, Andreas ; Allora & Calzadilla ; Fowler, Luke ; Bolf, Josef ; Cernicky, Jiri ; Kintera, Kristof ; Kiodová, Lenka ; Kovanda, Jiri ; Mancuska, Jano ; Ondák, Roman ; Pesko, Radim ; Jasanský, Lukás ; Polák, Martin ; Serych, Jan ; Skala, Jiri ; Vanek, Tomás ; Velcovsky, Maxim
FAIR was curated by students in the final year of the Royal College of Art's MA Curating Contemporary Art
biog. p.80-91, bibliog. p. 92-93
Engels
Fair, Royal College of Art, London, 19 - 24 March 2002
boek